Production Improvement through Fixture Design: A Case Study of an Agricultural Machinery Parts Manufacturer - Phontang, Bhoomboon; Pimollukanakul, Jetnipat; Gearam, Thamrong; Nithikarnjanatharn, Jittiwat; Muparang, Supattra; Nutkhum, Wannisa (RMUTL Engineering Journal, 2025)
This case study focuses on a manufacturing company producing agricultural machinery parts. The company faced a significant challenge: it could not meet customer demand due to inefficiencies in the production process. The primary objective of this study was to enhance the production process by implementing a new Jig Fixture and leveraging the principles of karakuri kaizen. Through a thorough analysis of the production process, the Customer revealed that the daily demand was 350 units, while the company could only produce 280 units per day. The researchers employed engineering principles to address this issue, including 7 QC Tools and Failure Mode and Effects Analysis (FMEA). By identifying the root causes of the production bottlenecks, the team developed and implemented solutions involving a new workpiece holding device and Karakuri Kaizen automation. The results of these improvements were substantial. The cycle time per unit decreased from 96.22 seconds to 75.52 seconds, enabling the company to produce 362 daily units. The total production distance was reduced from 30.2 meters to 27.7 meters.